Penerapan Model Pembelajaran Berbasis Riset Berintegrasi Pendidikan Karakter Bagi Guru SMA/SMK Se-Kota Gorontalo - Nova Elysia Ntobuo; Asri Arbie; Lanto M. Kamil Amali (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
This activity aims to provide scholarly and skills for high school / vocational physics teachers on the application of research-based learning model integrated character education. The target in the implementation of this activity is increasing the knowledge and skills of the trainees, so that will have a positive impact on improving the skills, character and learning outcomes of students. In addition, through this activity is targeted the compilation of science learning devices by teachers of trainees by applying research-based learning model to integrate character education in Physics learning in SMA / SMK. The chosen method is to carry out training activities of the application of research-based learning model to integrate character education for high school teachers / vocational schools in Gorontalo city. The training activities will begin with the provision of materials on research-based learning models, character education, dissemination of research learning tools and simulations of the application of instructional learning tools. Furthermore, the following activities are guiding the preparation of learning tools and simulation of the devices that have been prepared. This dedication activity ends with the evaluation in the form of direct practice in each school which will be observed directly by the implementing team of IbM and the school supervisor. The results achieved in the implementation of this IbM activity is the Physics Teachers of SMA / SMK can design and develop learning tools through the application of research-based learning model to integrate character education and can apply it in the learning process, resulting 20 pieces Learning tools (including RPP, Teaching Materials, LKPD, Test of Learning Outcomes, student-based activity instruments and Student character appraisal instruments) compiled by participants of training activities.